Optimization of Investigation Services with SP2HP Online at Brebes Police in Realizing Precision Law Enforcement - Ragil Dimas Ramadhan (Police Studies Review, 2024)
This study is focused on how to optimize investigation services with SP2HP Online by the Brebes Resort Police Criminal Investigation Unit and determine factors that impede the use of SP2HP Online services in law enforcement at the Brebes Resort Police, as well as to describe investigation services with SP2HP Online by the Brebes Resort Police Criminal Investigation Unit. This study is significant because it corresponds to one of the points in the priority work program of the Chief of the Indonesian National Police, General Police Listyo Sigit Prabowo, M.Sc., which is the realization of the 4.0 police era and the establishment of the PRESISI of the Indonesian National Police. The problem that arises in this final project is related to "Why is the investigative performance of the Brebes Resort Police Criminal Investigation Unit with SP2HP Online to realize precision law enforcement still not optimal?" The main theoretical basis (Grand theory) in this study is the POAC Basic Management theory and Management Resource theory. To support the main theory, the researcher employs the SWOT Analysis theory as a Middle Theory. As for the concepts in this Final Project, they are as follows: Optimization, Service, Investigation, SP2HP Online, Reporting Rights, and Law Enforcement. The research method used in this study is a qualitative method. The type of research used is descriptive-qualitative. The research location is under the jurisdiction of the Brebes Resort Police, specifically the Brebes Police Criminal Investigation Unit. The results of the study show that there is a discrepancy in the use of SP2HP Online services as seen from organizational resources and management theory, which refers to the Regulation of the Chief of the Indonesian National Police No. 6 of 2019 concerning criminal acts investigations, the Regulation of the Chief of the Indonesian National Police No. 21 of 2011 concerning investigative information systems, and the Regulations of the Head of the Criminal Investigation Agency No. 1 of 2022. The implementation of these services is not compliant with applicable regulations, and the contents of the service are insufficient to meet the minimum SP2HP requirements. The suggestion offered is to conduct supervision and make efforts to familiarize investigators with using the e-investigation program in carrying out criminal investigations.